Artificial insemination in dromedary camels (Camelus dromedarius) using fresh semen extended by physical agitation for achieving liquefaction - CHOLAKKAL, IBRAHEEM KUTTY (The Indian Journal of Animal Sciences, 2019)
Artificial insemination (AI) is widely used in farm animals for efficient utilization of superior males. However, AI is not being used in camels due to various difficulties involved in the process. In an attempt to develop the technology in camels, the present study was carried out to assess the success rate of insemination using fresh semen mixed by physical agitation within the extender media for overcoming difficulties out of gel formation. The study was carried out utilizing 3 males and 10 female Omani camels. Starting from November 2015, 109 semen ejaculates were collected and good quality ejaculates were extended using Triladyl or Tris sucrose based extenders. Ejaculates added with the extender were subjected to physical stirring for 30 sec using plastic straws to achieve mixing of the ejaculate gel. Female camels were scanned regularly for ovarian activity, ovulation was induced and AI done using fresh extended semen doses having at least 100 million motile sperms. Seventeen AI in three rounds resulted in 9 pregnancies giving an overall conception rate of 53%. First insemination conception rate was 50% and 80% of the camels conceived at least by three AI. Various determinants of conception from AI in camels are discussed. It is concluded that insemination using fresh semen extended by physical agitation in Triladyl and Tris Sucrose extenders provided encouraging conception rate for developing AI technology in camels.